The quality of reporting randomized controlled trials in the dermatology literature in an era where the CONSORT statement is a standard. (25th December 2018) - Kim, D.Y.; Park, H.S.; Cho, S.; Yoon, H.S.
Summary: Background: The quality of reporting randomized controlled trials (RCTs) in the dermatology literature has not received much consideration since the late 2000s. Objectives: We aimed to assess the quality of recently reported RCTs published in dermatology journals, focusing on randomization processes, blinding and trial registration. Methods: We reviewed 2042 original articles and identified 141 primary reports of RCTs in four dermatology journals ( Journal of the American Academy of Dermatology, JAMA Dermatology, Journal of Investigative Dermatology and British Journal of Dermatology ) from January 2015 to December 2017. Details were extracted from articles, supplements and public trial registries. A multivariable logistic regression analysis was conducted to identify factors associated with optimal reporting quality. Results: Among the 141 RCTs, 99 (70·2%), 82 (58·2%) and 69 (48·9%) described methods used for randomization, allocation concealment and implementation, respectively. Most trials (126, 89·4%) reported blinding status; however, one‐third did not state the similarity of the intervention. Furthermore, 52 RCTs (36·9%) were not registered prospectively. Trials published in the British Journal of Dermatology and using central randomization were significantly associated with optimal reporting quality after adjusting for covariates. Conclusions: Several critical items in reporting RCTs, including allocation concealment, similarity of interventions in blinded trials and prospective trial registration, have remained unsatisfactory in the recent dermatology literature. Abstract : What's already known about this topic? The adoption of the CONSORT statement by journals has been associated with improved quality of reporting randomized controlled trials (RCTs). The quality of reporting RCTs in the dermatology literature was below an acceptable level in the early 2000s. What does this study add? Only 30·5% of RCTs recently published in four leading dermatology journals show optimal reporting quality. Reporting on the randomization processes used and prospective trial registration was suboptimal, while blinding status was reported in the majority of RCTs. Factors associated with optimal reporting quality on multivariable analysis included publication in the British Journal of Dermatology and use of central randomization. Linked Editorial: Kwatra and Kang. Br J Dermatol 2019; 180 :1277–1278 . Respond to this article